Analysis of Peculiarities of Epidemiological Situation on Cholera in the World and in the Russian Federation in 2024 and Forecast of its Development in 2025 - V. D. Kruglikov; N. E. Gaevskaya; E. V. Monakhova; E. A. Moskvitina; V. V. Agafonova; I. V. Savina; O. A. Podoynitsyna; N. A. Selyanskaya; A. S. Vodop’yanov; O. V. Duvanova; E. A. Men’shikova; M. I. Ezhova; et al. (Проблемы особо опасных инфекций)
The aim of the work was to analyze the peculiarities of the cholera epidemiological situation in the world and in Russia in 2024; forecast for 2025. The results of proactive epidemiological surveillance showed a continued upward trend in cholera morbidity in the world despite of the decrease in this indicator in 2024 (762 830 cases in 42 countries) as compared to 2023 (816 235 in 47 countries). A special feature was the import of a polyantibiotic-resistant Vibrio cholerae O1 El Tor strain from Tanzania to Island Mayotte. Active labor migration to the Russian Federation (RF) from countries with unfavorable cholera situation was noted (11 686 foreigners, 88.17 % – from India). No cholera patients (vibrio carriers) were identified in RF. The features of epidemiological situation have been established: two toxigenic V. cholerae O1 strains similar to the one isolated in 2023, and one toxigenic strain of NAG, documented in RF for the first time, were detected in surface water bodies. It has been determined that the non-toxigenic V. cholerae O1 strain, which caused a case of acute intestinal infection, and waterborne O1 strains circulating in Russia belong to the same clone. For the first time, the non-toxigenic V. cholerae O139 strain was isolated from a patient with acute intestinal infection. An increase in the number of non-toxigenic O1 strains isolated from water bodies was noted (335 in 2024, 52 in 2023), mainly due to the clonal complex (250 strains, Krasnodar Territory) spread through karst waters. Diseases caused by non-toxigenic NAG vibrios V. parahaemolyticus and V. fluvialis, were detected. The forecast for 2025 covers the risks of cholera importation, including cases caused by antibiotic-resistant strains; increase in labor migration from countries with an unfavorable cholera situation; the likelihood of detecting toxigenic O1 and nonO1/nonO139 strains in the environment, an increase in the number of acute intestinal infections caused by non-toxigenic cholera and other pathogenic vibrios; possible detection of extra-intestinal infections, an increase in the number of non-toxigenic V. cholerae O1 in environmental objects. It is advisable to start monitoring studies earlier (April) and finish them later (October) in RF in 2025 in type I territories classed according to epidemic manifestations of cholera.